2019
DOI: 10.1016/j.quaint.2018.09.040
|View full text |Cite
|
Sign up to set email alerts
|

Tephra in caves: Distal deposits of the Minoan Santorini eruption and the Campanian super-eruption

Abstract: Tephra deposits in caves are not only significant as stratigraphic markers. The comparatively sheltered position of cave environments, protected from rainfall, may preserve original distal tephra deposition features, unlikely to have survived in the open landscape. Most reported findings of tephra in caves are from the Campanian supereruption, which originated in the area of Naples (Italy). These findings facilitate evaluation in different caves of facies variability and modes of tephra deposition, derived fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…The CI tephra occurs in the above-mentioned sites either as a relatively proximal, thick primary pyroclastic succession (e.g., Serino openair site; Accorsi et al, 1978;Giaccio et al, 2006) or as a discrete layer, with a sharp lower contact with underling sediments, made of purely volcanic material (i.e., glass shards or pumice fragments with mineral accessories) with no or negligible contamination by clastic sediments. These features are consistent with a sub-primary (re)deposition of ash layers by the wind or run-off shortly after its emplacement as primary fallout along landforms nearby sheltered or open-air archaeological sites (e.g., Bruins et al, 2019). Specifically, at Castelcivita site, both Plinian pumice and co-ignimbritic ash layers are recorded in their eruptive stratigraphic order, suggesting that the two eruptive units were transported and redeposited in the cave immediately after their fall (fall and rolling process) (Giaccio et al, 2008;Giaccio et al, 2006).…”
Section: The Campanian Ignimbrite (Ci) Markersupporting
confidence: 70%
“…The CI tephra occurs in the above-mentioned sites either as a relatively proximal, thick primary pyroclastic succession (e.g., Serino openair site; Accorsi et al, 1978;Giaccio et al, 2006) or as a discrete layer, with a sharp lower contact with underling sediments, made of purely volcanic material (i.e., glass shards or pumice fragments with mineral accessories) with no or negligible contamination by clastic sediments. These features are consistent with a sub-primary (re)deposition of ash layers by the wind or run-off shortly after its emplacement as primary fallout along landforms nearby sheltered or open-air archaeological sites (e.g., Bruins et al, 2019). Specifically, at Castelcivita site, both Plinian pumice and co-ignimbritic ash layers are recorded in their eruptive stratigraphic order, suggesting that the two eruptive units were transported and redeposited in the cave immediately after their fall (fall and rolling process) (Giaccio et al, 2008;Giaccio et al, 2006).…”
Section: The Campanian Ignimbrite (Ci) Markersupporting
confidence: 70%
“…Research on Santorini's distal tephrostratigraphy was initiated in the 1960s by the first detection of the Minoan (Z-2) tephra in Eastern Mediterranean deep-sea sediments (e.g., Heezen, 1965, 1967;Keller and Ninkovich, 1972;Keller et al, 1978;Watkins et al, 1978;Vinci, 1985), on the islands of Crete, Milos and Rhodes (e.g., Vitaliano and Vitaliano, 1974;Doumas and Papazoglou, 1980;Bruins et al, 2019), and in Asia Minor (e.g., Sullivan, 1988). Subsequent studies of marine sediment cores from the southern Aegean and Levantine Seas identified six further visible tephra layers of Santorini provenance in deeper stratigraphic positions that, according to their occurrence in different foraminiferal stratigraphic zones, are labelled as Y-2 (CR), Y-4 (Cape Tripiti), X-1 (USC1), W-2 (MP), V-1 (LP2) and V-3 (LP1) tephras (e.g., Keller et al, 1978;Federman and Carey, 1980;Vinci, 1985;Fabbro et al, 2013) (Fig.…”
Section: Santorini's Distal Tephrostratigraphic Record: State Of the Artmentioning
confidence: 99%
“…Eden et al, 1992Eden et al, , 1996Neall et al, 2001;Matsu'ura et al, 2012;Obreht et al, 2016), and caves and rock shelters, have also yielded cryptotephras (e.g. Barton et al, 2015;Bruins et al, 2019;Hirniak et al, 2020), as have stalagmites (Klaes et al, 2022). Here, we list further examples including benchmark methodological papers, regional reviews, and recent papers on long sedimentary sequences that collectively emphasize the growing importance of cryptotephrochronological research: Turney (1998), Hunt (1999b), Hall and Pilcher (2002), van den Bogaard and Schmincke (2002), Davies et al (2004), Gehrels et al (2008, Wastegård and Davies (2009), Swindles et al (2011, 2019, Lawson et al (2012), Matsu'ura et al (2012, Wastegård and Boygle (2012), , Riede andThastrup (2013), Smith et al (2013), Abbott et al (2018aAbbott et al ( , b, 2020a, Menke et al (2018), Wulf et al (2018), , Leicher et al (2019), Jones et al (2020), Freundt et al (2021, Jensen et al (2021), andKinder et al (2021).…”
Section: Development Of Cryptotephra Studies and The Advent Of The Mo...mentioning
confidence: 99%
“…We record the names of those who have held positions as elected officers or who convened conferences or workshops on behalf of the global tephra community. The contributions of various individuals to the discipline of tephrochronology, addressed in some cases in our article, have been reported in special editorials, historical articles, or obituaries (see Einarsson, 1982;Vucetich, 1982;Björnsson, 1983;Royal Geographical Society, 1983;Noe-Nygaard, 1984;Steinthórsson, 1985Steinthórsson, , 2012Lowe, 1990a;Wilson, 2005;Self and Sparks, 2006;Tonkin and Neall, 2007;Froese et al, 2008b;Lowe et al, 2008aSlate and Knott, 2008;Hunt, 2011;Moriwaki et al, 2011a;Benedik-tsson et al, 2012a;Alloway et al, 2013;Kile, 2013;Thomas and Lamothe, 2014;Lundqvist et al, 2019;Bunting et al, 2020;Mazei et al, 2020;Hopkins et al, 2021a;Stork-Bullock Mortuary, 2021).…”
Section: Reviewing the Commission On Tephrochronology (Cot)mentioning
confidence: 99%
See 1 more Smart Citation